Experimental and transient thermal analysis of screen mesh wick heat pipe. (2021) - Ch Nookaraju, B.; Keziya Rani, P.; Kurmarao, P.S.V.; Naga Sarada, S.; Sateesh, N.; Anitha Lakshmi, A.; Subbiah, Ram
Abstract: Transient thermal analysis of a screen mesh wick heat pipe is performed with a screen mesh numbers 60 and 100 using de-ionized water as working fluid, which is applicable in electronics cooling. Based on evaporation and condensation phenomenon heat pipe is operating. Experiments are conducted (ranging from 20Watts-160Watts) with different inclination angles (15, 30, 60, 90) for calculation of thermal resistance(Rth ) and heat transfer coefficient (h), at different mass flow rates and heat inputs. Computational transient thermal analysis is done for the same heat inputs using ANSYS 16.0. It is observed that thermal resistance decreases with increase in heat input [maximum at 0.042(°C//W), minimum at 0.023 (°C/W)] because fluid molecular bonding decreases with increase in heat input. Heat transfer coefficient values are maximum at 8800 (W/m 2 K) for transient thermal analysis and 8500 (W/m 2 K) for experimental. The Heat transfer coefficient is more in thermal analysis when compared to experimental results because heat loss is less in ANSYS and more in practical. At 60 W of heat input the maximum Heat transfer coefficient is found.